2012
DOI: 10.1073/pnas.1115467109
|View full text |Cite
|
Sign up to set email alerts
|

A novel lineage of myoviruses infecting cyanobacteria is widespread in the oceans

Abstract: Viruses infecting bacteria (phages) are thought to greatly impact microbial population dynamics as well as the genome diversity and evolution of their hosts. Here we report on the discovery of a novel lineage of tailed dsDNA phages belonging to the family Myoviridae and describe its first representative, S-TIM5, that infects the ubiquitous marine cyanobacterium, Synechococcus. The genome of this phage encodes an entirely unique set of structural proteins not found in any currently known phage, indicating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(136 citation statements)
references
References 40 publications
3
133
0
Order By: Relevance
“…Our analysis does not include the highly divergent non-T4-like cyanomyovirus described recently by Sabehi et al (2012) as it was not available when we began the work. We compared the frequencies of genes in cyanomyovirus genomes in three marine environments to identify genes that the environments have in common and genes that distinguish them.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis does not include the highly divergent non-T4-like cyanomyovirus described recently by Sabehi et al (2012) as it was not available when we began the work. We compared the frequencies of genes in cyanomyovirus genomes in three marine environments to identify genes that the environments have in common and genes that distinguish them.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of cyanobacteria, it has been further suggested that most HGT are mediated by phages (cyanophages) (e.g. Sullivan et al 2010;Sabehi et al 2012). These phages often contain genes important in photosynthesis (Zheng et al 2014).…”
Section: Speciation Factors In (Cyano)bacteriamentioning
confidence: 99%
“…Similarly, most cyanophages have been isolated using a few strains of Synechococcus spp. ; however, a previously unknown lineage of myoviruses (S-TIM5) was isolated from the Red Sea using a different Synechococcus strain (Sabehi et al, 2012). Clearly, there is enormous potential to isolate representatives of previously unknown groups of viruses by screening untested taxa of host organisms.…”
Section: Genomic Analysismentioning
confidence: 99%
“…Host-range studies have revealed that some cyanophages have broad host ranges and are able to infect strains that are distantly related (Suttle and Chan, 1993;Waterbury and Valois, 1993) or that even belong to different genera (Sullivan et al, 2003). Nonetheless, the mosaic architecture of phage genomes, including structural genes that result in similar morphology but that appear to have a different evolutionary origin (Sabehi et al, 2012), increasingly call into question the use of a Linnaeanbased hierarchical classification, including morphology, as a basis for classifying phage (Lawrence et al, 2002;Nelson, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation